Peranan Hubungan Industrial Pancasila dalam Penyelesaian Konflik Ketenagakerjaan di Indonesia - Naufal Varis Rajaudin; Matsna Noor Mannan Achmad Zhidan; Rizal Aditya; Adib Mustofa (Jurnal Pelita Nusantara, 2026)
This study aims to: (1) analyze the implementation of Pancasila Industrial Relations (HIP) in resolving industrial relations disputes in Indonesia, (2) identify factors that hinder HIP implementation, and (3) formulate strategies to increase HIP's effectiveness in addressing the dynamics of industrial relations in the era of globalization. This study uses a normative legal research method with a statutory and conceptual approach. The data sources used are secondary data consisting of primary legal materials (laws and regulations in the field of employment and industrial relations), secondary legal materials (books, scientific journals, and previous research results), and tertiary legal materials (legal dictionaries and encyclopedias). Data collection techniques were conducted through literature review. The data analysis technique used qualitative analysis with a descriptive-analytical approach. The results of the study indicate that the implementation of the Industrial Relations Dispute Resolution System (HIP) in resolving industrial relations disputes prioritizes the principles of deliberation, consensus, and social justice, which contribute to creating harmonious working relationships. However, in practice, various obstacles remain, including the weak bargaining position of workers, suboptimal law enforcement, and the suboptimal internalization of Pancasila values within the corporate environment. Therefore, a strategy is needed to strengthen the HIP by increasing the government's role as regulator and supervisor, strengthening the capacity of labor unions, and increasing employer commitment to integrating Pancasila values into the work culture.